1987
DOI: 10.1111/j.2044-8260.1987.tb01367.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the National Adult Reading Test hold in dementia?

Abstract: Thirty elderly subjects with a clinical diagnosis of dementia were assessed using a neuropsychological test battery and were retested one year later. No significant deterioration in performance on the National Adult Reading Test (NART) was observed. A significant deterioration was noted in performance on the Mill Hill Vocabulary Scale synonym section (MHVS). Expected significant decrements in Clifton Assessment Procedures for the Elderly (CAPE) Information/Orientation and Physical disability scales were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
3

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 3 publications
2
23
0
3
Order By: Relevance
“…First, similar to the previous studies with NART [7, 10, 27], our data showed that the KART was relatively poor in predicting performance IQ. Thus, users must be cautious when using the KART to estimate premorbid performance IQ.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…First, similar to the previous studies with NART [7, 10, 27], our data showed that the KART was relatively poor in predicting performance IQ. Thus, users must be cautious when using the KART to estimate premorbid performance IQ.…”
Section: Discussionsupporting
confidence: 88%
“…Main rationale for such tests is that reading ability is shown to be resistant to mental deterioration due to organic causes [6]. Previous studies have demonstrated that performance on a word reading test is resistant to deterioration in patients with mild to moderate dementia of different etiologies and that its scores are stable after one year of progressive declines in other cognitive functions [710]. …”
Section: Introductionmentioning
confidence: 99%
“…Correlations of consistently more than 0.9 have been shown between different raters (O'Carroll, 1987).…”
mentioning
confidence: 97%
“…One well‐established example of the application of hold tests in this context is the use of the National Adult Reading Test (NART) to predict premorbid IQ scores (e.g. Crawford et al , 1998; Crawford, Parker, & Besson, 1988; O'Carroll, Blaikie, & Whittick, 1987). For older persons, NART scores can be superior to years of formal education as a means of incorporating educational attainment into regression equations, since time at school for past generations often reflected opportunity rather than ability.…”
mentioning
confidence: 99%